2021
DOI: 10.1002/hep.31809
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Mercury Is Associated With Increased Susceptibility to Liver Injury and Inflammation in Childhood

Abstract: Background and Aims Nonalcoholic fatty liver disease (NAFLD) is the most prevalent cause of liver disease in children. Mercury (Hg), a ubiquitous toxic metal, has been proposed as an environmental factor contributing to toxicant‐associated fatty liver disease. Approach and Results We investigated the effect of prenatal exposure to Hg on childhood liver injury by combining epidemiological results from a multicenter mother–child cohort with complementary in vitro experiments on monocyte cells that are known to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
1
17
1
Order By: Relevance
“…Prenatal exposures to PFASs and mercury were previously associated with elevated ALT levels and liver injury in children in the HELIX project. 17,18 Previous cross-sectional studies 16,50 reported positive associations between the plasma or serum concentration of PFASs, including perfluorooctanoic acid, perfluoro-octane sulfonate, perfluorononanoic acid, and perfluorohexane sulfonate, and liver enzyme levels and/or nonalcoholic steatohepatitis in US children. Similarly, among metals, mercury exposure had been linked to elevated ALT levels in adolescents in the US NHANES 51 and increased ALT and GGT levels in adults from South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal exposures to PFASs and mercury were previously associated with elevated ALT levels and liver injury in children in the HELIX project. 17,18 Previous cross-sectional studies 16,50 reported positive associations between the plasma or serum concentration of PFASs, including perfluorooctanoic acid, perfluoro-octane sulfonate, perfluorononanoic acid, and perfluorohexane sulfonate, and liver enzyme levels and/or nonalcoholic steatohepatitis in US children. Similarly, among metals, mercury exposure had been linked to elevated ALT levels in adolescents in the US NHANES 51 and increased ALT and GGT levels in adults from South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…This conflicting data may be in part due to the potential biphasic effects of such toxins in either activating or blunting the immune system, especially in the case of cadmium [ 110 ], or may indicate that other factors such as maternal metabolism or immune responsivity may influence the effects of these xenobiotics. Importantly, exposure to heavy metals such as arsenic, lead, cadmium and mercury have all been associated with increased immune activation, and specifically enhanced IL-6 and IFNγ production, in several preclinical and clinical contexts [ 111–116 ]; however, systematic in vivo studies evaluating these compounds’ effects on cytokine levels in the developing brain is still required. While there is a strong association between immune-activating external stressors (e.g., viral infections, pollution and other toxins) and neurodevelopmental abnormalities that may manifest as ASD, further preclinical and clinical research is needed to fully understand the mechanisms by which these extrinsic factors directly influence fetal neurogenesis and neurodevelopmental abnormalities.…”
Section: Maternal Immune Activation (Mia) and Autism Spectrum Disorde...mentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease in most regions of the world. It is a cause of the high incidence of end-stage liver disease worldwide and an inducer of hepatocellular carcinoma (HCC) [1,2]. A study showed that the total prevalence of NAFLD in China from 1999 to 2018 was 29.6% (95% CI: 28.2-31.0%), and the total number of patients with NAFLD in China is expected to increase to 314.58 million by 2030 [3].…”
Section: Introductionmentioning
confidence: 99%